Design and Development of a Smart Cat Litter Box - Burhanuddin, Muhammad Irfan; Hassan, Mohd Fahrul; Abdul Hamid, Mohd Hamisa (Research Progress in Mechanical and Manufacturing Engineering, 2026)
The increasing demand for efficient cat litter management stems from challenges like odors, residue buildup, and unreliable self-cleaning systems. These issues often require manual intervention, creating inconvenience for pet owners. This study follows George E. Dieter’s design methodology, covering conceptual, embodiment, and detailed design phases. Customer feedback gathered through surveys helped shape the product concept. SolidWorks was used for 3D modeling and structural analysis to refine the design. The smart cat litter box includes automated cleaning and litter dispensing systems to reduce odors and minimize manual maintenance. A proof-of-concept prototype confirmed the design’s effectiveness. The final product measures 34 cm by 54.5 cm by 60 cm, and weighs 15.37 kg, providing a compact, efficient, and user-friendly solution for pet owners.